Ochratoxin A in roasted coffee commercially sold in the city of Rio de Janeiro - Marco Antonio Mota; Vanessa Elen de França Valle; Maria Heloísa Paulino Moraes; Elaine Santos Lima (Fundação Oswaldo Cruz (FIOCRUZ), 2015)
The objective of this study was to evaluate the incidence of ochratoxin A (OTA) in roasted and ground coffee commercially sold in Rio de Janeiro in 2002-2003 and 2012-2013. Samples were prepared using an immunoaffinity column, and OTA was quantified by HPLC using a fluorescence detector (LOD of 0.3 µg·kg−1 and LOQ of 0.7 µg·kg−1). In total, 29 samples were collected in 2002-2003, with 12 samples containing levels below the LOD and 17 samples containing levels in the range of 0.3-5.7 µg·kg−1. In the monitoring conducted in 2012-2013, 37 samples were evaluated, with only 02 samples having levels below LOD. The remaining 35 samples had levels in the range of 0.3-3.1 µg·kg−1. OTA concentrations in all samples were lower than the maximum tolerable limit set by the Brazilian legislation (10 µg·kg−1). However, it is relevant to stress the importance of OTA control in coffee as a product consumed daily by Brazilians.